High-level Collaboration Between the Public Sector and Religious and Faith-based Organizations : Fad or Trend? - Duff, Jeff; Battcock, Mike; Karam, Azza; Taylor, Adam Russell (Taylor and Francis, 2016)
Progress towards shared Global Goals—the Millennium Development Goals, and now the Sustainable Development Goals (SDGs)—calls for an inclusive “all hands on deck” approach. The holistic approach of the SDGs offers a common framework for harnessing the distinctive assets of religious and faith-based organizations (RFBO) in national plans and global collaborations towards their achievement. Despite the challenges associated with forging collaboration across sectors, cultures, and value systems, we see signs of more sophisticated collaboration between public sector and RFBOs. These include a greater focus on evidence and cross-sector dialogue, new coordinating mechanisms, and renewed commitments to partnership.